2018
DOI: 10.1049/iet-pel.2017.0594
|View full text |Cite
|
Sign up to set email alerts
|

Improvised predictive torque control strategy for an open end winding induction motor drive fed with four‐level inversion using normalised weighted sum model

Abstract: Open end winding induction motor (OEWIM) drives are better alternate for multi-level inverter fed induction motor drives. OEWIM drives can be used in industries and electric vehicles but they entail ripple-free torque. Predictive torque control (PTC) strategy offers high dynamic performance and lesser ripple in torque, flux when compared with direct torque control. Classical PTC involves high switching frequencies and empirical methods to select weighting factors. The selection and tuning of weighting factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
(56 reference statements)
0
18
0
1
Order By: Relevance
“…Now, by comparing the (26) and (30), the coefficients k p and k i of the PI torque controller can be calculated by…”
Section: Proposed Predictive Flux Control (Pfc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Now, by comparing the (26) and (30), the coefficients k p and k i of the PI torque controller can be calculated by…”
Section: Proposed Predictive Flux Control (Pfc)mentioning
confidence: 99%
“…Various attempts have been made to derive an optimal value for the weighting factor through adopting an online optimization technique which updates the weighting factor according to the instantaneous change of the controlled variables respecting to their references [25], [26]. The disadvantage of this technique is that it adds extra computation burdens on the controller which cannot be realized by all microprocessors.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of MPC in motor drives area is arising and still largely unexplored. A huge amount of research can found for induction motor systems that used MPC [38][39][40][41]. An important research related to PMSM with MPC is given in [21,[42][43][44][45].…”
Section: Permanent Magnet Synchronous Reluctance Motormentioning
confidence: 99%
“…The classical DTC and PTC strategies give higher ripples in torque and flux. Generally, lesser torque and flux ripples can be obtained by using constant switching frequency, duty ratio control, or MLI [16][17][18][19][20][21][22]. DTC with constant switching frequencies can be obtained using space vector modulation (SVM).…”
Section: Introductionmentioning
confidence: 99%